Transfer Pricing: Pajak, Mekanisme Bonus, Kontrak Hutang, Nilai Tukar dan Multinasionalitas - Rosita Wulandari; Dwi Nur Anisa; Wiwit Irawati; Ali Mubarok (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
Obtaining empirical evidence regarding the effect of taxes, bonus mechanisms, debt contracts, exchange rates and multinationals on transfer pricing decisions is the aim of this study on manufacturing sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Quantitative type in this study. The sample used was 40 data based on purposive sampling method. The method of analysis in this study is Panel Data Regression. The results of this study prove that debt contracts have an effect on transfer pricing decisions, while taxes, bonus mechanisms, exchange rates, and multinationality have no effect on transfer pricing decisions.